Representasi Kasta Sudra Dalam Cerpen Kharma Phala Karya Ni Wayan Wijayanti - Poetri, Maharanny Setiawan (Peneliti.net, 2024)
Representation is a form of words, images, stories, and others that represent an idea, emotion, or fact. Representation can take the form of speaking or acting on behalf of the person or situation described. Representation can also mean describing someone or something in a certain way. This study aims to examine the representation of the Sudra caste. The method used in this research is descriptive-qualitative. The representation of the Sudra caste is described through the lens of Stuart Hall's theory of representation, based on data from the short story Kharma Phala as the data source. The results of the study indicate that backwardness, poverty, and dirtiness are the representations of the Sudra caste depicted in the short story Kharma Phala by Ni Wayan Wijayanti